Autorytarna władza Prezydenta Rzeczypospolitej Polskiej w myśli Stanisława Cara - Srokosz, Jacek (Wydawnictwo Uniwersytetu Wrocławskiego, 2009)
In this article the author attempts to demonstrate the authoritarian elements present in the political-and-legal thought of Stanisław Car, one of the creators of the April Constitution, who manifested themselves by granting the dominating position in the state to the President. The foundation of Car’s conception was the rejection of the ideas of popular sovereignty, of separation of powers as advocated by Montesquieu and of parliamentarian rule. Instead, Car suggested conferring sovereignty and granting uniform and indivisible power to the head of state, namely the President. Supreme power in the state was supposed to lie in his hands. He was to be an arbiter in disputes between other branches of power and to set the general directions of state’s policy through the issue of directives for other branches of power. As the head of state, President was not to be subject to any institutionalized state control and to be responsible for his political and legal activities undertaken while in office. He was supposed to be responsible only “before God and history”. Other branches of power were to remain under his supremacy. The executive branch was to be very strongly subordinated to the head of state. The government was supposed to be appointed and dismissed by the President. It was also responsible to him for its actions. In relation to the parliament the President’s position was to be strengthened by granting him the right to convene and close its sessions, the right to issue ordinances with statutory power, and the right to appoint 1/3 of the members of the senate. President was to be elected by electoral college so-called Electoral Assembly. However, the retiring head of state had to accept the candidate proposed by this body. If he put forward another name, the general election would have to take place in which voters would choose between the two candidates. Based on these constitutional postulates, the author of this article demonstrates that Stanisław Car’s concepts adopted the authoritarian mode of the exercise of power by the head of state. The projected system was in fact created for one person – Jozef Piłsudski, and was an attempt to legally legitimize the factual practices of “sanacja”.
Keywords: Car, Stanisław (1882-1938); authoritarianism; President of the Second Polish Republic; power